Chapter Primi appunti sulla tradizione del Filostrato: strategie d'approccio e questioni di metodo - Vitolo, Raffaele (Studi e saggi, 2022)
The study here discussed presents the tradition of the Filostrato and the editorial history of the text. The criteria for the ecdotic analysis of the manuscrupts are also shown in the perspective of a future critical edition. The varia lectio is then exemplified by presenting some loci.